Spontaneous closure of traumatic tympanic membrane perforations: observational study. Issue 10 (7th September 2015) - Jellinge, M E; Kristensen, S; Larsen, K
Abstract Background: The treatment of traumatic tympanic membrane perforations varies in different investigations, ranging from observation to early surgical repair. The present study aimed to focus on the closure rate and the closure time in a group of patients treated with a watchful waiting policy. Methods: The study comprised 133 consecutive patients with a total of 137 perforations. Data were evaluated in terms of aetiology, location and size of perforation, audiometric findings, closure rate, and closure time. Results: The overall closure rate was 97 per cent. For patients with a known closure time within three months, the median closure time was between three and four weeks. The probability of spontaneous closure over time was further analysed with Kaplan–Meier plots, for those perforations with known closure times and for all perforations including those with unknown closure times. Perforation size was the only significant determining factor for closure time. Conclusion: Small perforations had a high probability of spontaneous closure within three to four weeks, justifying a watchful waiting policy. Larger uncomplicated perforations might warrant early surgical repair, depending on the patient's needs and the availability of surgery.